The differential view of genotype–phenotype relationships - Orgogozo, Virginie; Morizot, Baptiste; Martin, Arnaud (Frontiers in Genetics, 2015)
An integrative view of diversity and singularity in the living world requires a better understanding of the intricate link between genotypes and phenotypes. Here we re-emphasize the old standpoint that the genotype-phenotype relationship is best viewed as a connection between two differences, one at the genetic level and one at the phenotypic level. As of today, predominant thinking in biology research is that multiple genes interact with multiple environmental variables (such as abiotic factors, culture, or symbionts) to produce the phenotype. Often, the problem of linking genotypes and phenotypes is framed in terms of genotype and phenotype maps, and such graphical representations implicitly bring us away from the differential view of genotype-phenotype relationships. Here we show that the differential view of phenotype-genotype relationships is a useful explanatory framework in the context of pervasive pleiotropy, epistasis and environmental effects. In such cases, it is relevant to view genotype-phenotype relationships as differences embedded into differences. Thinking in terms of differences clarifies the comparison between environmental and genetic effects on phenotypes and helps to further understand the connection between genotypes and phenotypes.